Building the supply of inclusive sport. (17th December 2010) - Downs, Peter
Abstract : Australia is a large continent divided into eight states and territories with a population of 20 million. Australia also has a strong sport culture and a proud record of international success across a range of sports. The culture and philosophy of 'give it a go' lends itself to the notion of inclusion. In 1995 the Australian Sports Commission embarked on establishing a national programme to improve the supply of inclusive sport to the community. A national education programme was established, delivered through a network of partners. Resources were developed, including training courses, manuals, procedures and multi-media tools. By 2005 over 50 000 people had undergone training in inclusive practices within the sport industry. Establishing a national network and delivery system in a country the size of Australia was not without its challenges. This presentation will chart the progress Australia has made in this area and outline its plans to connect the demand for inclusive sport with the supply to increase participation in the long term.